Pengaruh penambahan tepung ubi jalar ungu (Ipomoea batatas L.) dan tepung umbi porang (Amorphophallus oncophyllus) terhadap karakteristik fisikokimia dan organoleptik biskuit - Deny Utomo; Dini Octasari (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Biscuits are snacks made from flour and fat that are baked and have a long shelf life. Biscuits contain carbohydrates, fats and calories which are high but low in fiber, vitamins and minerals. This study aims to determine the proportion of the addition of purple sweet potato flour and elephant foot tuber flour to the best physicochemical and organoleptic properties of biscuits. Method: This method used in the study of purple sweet potato flour and elephant foot flour biscuits was a randomized block design with 5 treatment substitutions and 3 replications, resulting in 15 trials. Results:The best results for biscuits were in the P5 treatment (17.5% purple sweet potato flour : 12.5% elephant foot tuber flour) with the results of the physicochemical analysis of fracture strength of 13.07 N, antioxidant activity of 81.88 mg/ml, moisture content of 3.11%, ash content of 1.74% and organoleptic test of taste 4.00 (like), aroma 4.00 (like), color 2.88 (rather like) and texture 4.08 (like). Conclusion: Treatment substitution with the addition of purple sweet potato flour and elephant foot tuber flour had a significant effect on the parameters of breaking strength, antioxidant activity, moisture content, ash content, taste, color and texture. But it has no real effect on the flavor.